FISH FAUNA OF KEDAR VALLEY, CHAMOLI-GARHWAL - Baloni, S P (Indian Journal of Fisheries, 2011)
No attempt seems to have been made so far to explore the fish fauna of Kedar Valley, inspite of the richness of water resources and zoogeographical significance. Kedar valley is in Chamoli-Garhwal and is situated in North latitude 30Â°-47’ and East longitude 79Â°^8’. The main river of this valley is Mandakini with a number of tributaries. River Mandakini originates at an altitude of 3583 metres at the southeastern base of Kedarnath peak, north latitude 30Â°-47’ and east longitude 79Â°-8’. The fishes were poUected both from the river and its tributaries.